Interleukin-22 Deficiency Reduces Angiotensin II-Induced Aortic Dissection and Abdominal Aortic Aneurysm in ApoE-/- Mice. (18th March 2022) - Wang, Yuan; Li, Juanjuan; Xu, Yulin; Liao, Shichong; Song, Junlong; Xu, Zhiliang; Wei, Wen; Zhu, Shan
Abstract : Background. Our previous study showed that interleukin-22 (IL-22) levels were increased in patients with aortic dissection (AD). This study evaluated the effects of IL-22 on AD/abdominal aortic aneurysm (AAA) formation in angiotensin II (Ang II)-infused ApoE-/- mice. Methods. ApoE-/- mice were treated with Ang II for 28 days, and IL-22 expression was examined. In addition, the effects of IL22 deficiency on AAA/AD formation induced by Ang II infusion in ApoE-/- mice were investigated. ApoE-/-IL-22-/- mice were transplanted with bone marrow cells isolated from ApoE-/- mice or ApoE-/-IL-22-/- mice, and AAA/AD formation was observed. Results. IL-22 expression was increased in both the aortas and serum of ApoE-/- mice after Ang II infusion and was mainly derived from aortic CD4+ T lymphocytes (CD4+ TCs). IL-22 deficiency significantly reduced the AAA/AD formation as well as the maximal aortic diameter in Ang II-infused ApoE-/- mice. Decreased elastin fragmentation and reduced fibrosis were observed in the aortas of ApoE-/-IL-22-/- mice compared with ApoE-/- mice. The deletion of IL-22 also decreased aortic M1 macrophage differentiation, alleviated M1 macrophage-induced oxidative stress, and reduced aortic smooth muscle cell loss. Furthermore, M1 macrophage-induced oxidative stress was worsened and AAA/AD formation was promoted in ApoE-/-IL-22-/- mice that received transplanted bone marrow cells from ApoE-/- mice compared with those that were transplanted with bone marrow cells isolated from ApoE-/-IL-22-/- mice. Conclusions. IL-22 deficiency inhibits AAA/AD formation by inhibiting M1 macrophage-induced oxidative stress. IL-22 potentially represents a promising new target for preventing the progression of AAA/AD.